Infrared Spectroscopy for Studying Foods and Biodegradable Packaging - Shulga, Oksana; Chorna, Anastasia; Arsenieva, Larisa; Shulga, Sergii (My University, 2016)
The results of study of foods and biodegradable film structure with the use of infrared spectroscopy (IR spectra) are presented. For the first time detailed decodings of IR spectra of some foods and biodegradable film packaging materials are shown. Interpretation of the spectra of basic biopolymers of foods and biodegradable films is given. It is corroborated with the help of IR spectra that the chemical reactions in biopolymers when heated to 130 °C do not occur, which makes it possible to use biologically valuable raw materials. Furthermore, the expediency of use of IR spectroscopy for studying changes in foods and films produced on biopolymer base is established. IR spectroscopy is a fast method that allows you to monitor changes that occur with the raw materials in the technological process. Previously, IR spectroscopy was used to identify the compounds in chemical synthesis. This study shows that IR spectra can be used for study of foods and biodegradable film structure.
Keywords: IR spectra; biodegradable films; foods; biopolymers; starch; ІЧ спектр; біодеградабельні плівки; харчові продукти; біополімери; крохмаль; ИК спектр; биоразлагаемые пленки; пищевые продукты; биополимеры; крахмал; кафедра експертизи харчових продуктів